2020
DOI: 10.1108/md-09-2019-1329
|View full text |Cite
|
Sign up to set email alerts
|

Microdivisionalization as a way toward dynamic capability

Abstract: PurposeAs entrepreneurial top management teams in multidivisional forms are typically treated in pertinent literature as the default organizational solutions for developing dynamic capabilities, the emerging innovative organizational forms tend to be overlooked, even though they could be a viable means of transforming established enterprises. The present case study examines how Haier's microenterprise and platforms influenced the firm's dynamic capabilities development.Design/methodology/approachThe paper pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The literature indicates that the management systems of companies using the concept of dynamic capabilities should be characterized by a high level of decentralization [ 91 93 ], providing flexibility and allowing a rapid response to changes in the environment. This is also the view expressed by Volberda and Elfring, according to which developing dynamic capabilities requires the use of an adhocratic structure, in terms of Mintzberg, or an organic structure [ 94 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature indicates that the management systems of companies using the concept of dynamic capabilities should be characterized by a high level of decentralization [ 91 93 ], providing flexibility and allowing a rapid response to changes in the environment. This is also the view expressed by Volberda and Elfring, according to which developing dynamic capabilities requires the use of an adhocratic structure, in terms of Mintzberg, or an organic structure [ 94 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the Chen et al (2021) paper, the other two papers by Ferreira et al (2021) and the Bhasin and Found (2021) also demonstrate the benefits of modularity by binding different parts of an organization and working with external alliance partners to achieve a common investment end. By recognizing this and the “non-redeployability” or specificity of their complementary offerings and associated resource bases, it is clear that by making the joint objective of value creation the priority, the inevitable existence of incomplete contracts do not constrain; “ecosystems add value as they allow managers to coordinate their multilateral dependence through sets of roles that face similar rules, thus obviating the need to enter into customized contractual agreements with each partner” (Jacobides et al , 2018, p. 2,255).…”
Section: Towards a Theory Of Enablementmentioning
confidence: 95%
“…The first paper by Chen et al (2021), Microdivisionalization as a way toward dynamic capability , uses single case study techniques to understand if Haier's innovativeness is related to how company headquarters interacts with its microdivisions. The authors found that consistent with Teece's (2007) microfoundations of (sustainable) enterprise performance framework, the innovation routines established at Haier's over 2,000 microdivisions, in conjunction with a loosely coupled relationship with head office, are key to explaining Haier's success.…”
Section: Towards a Theory Of Enablementmentioning
confidence: 99%
See 2 more Smart Citations